Penerapan Kecerdasan Buatan dalam Perlindungan Hak Cipta: Studi Kasus pada Video Reaksi di YouTube - Islami, Ainul Fadilah Puji (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2025)
The development of digital technology, especially through YouTube, has given rise to a variety of creative content, including reaction videos. Despite their popularity, reaction videos often involve the unauthorised use of other parties' copyrighted works, potentially violating Law No. 28/2014 on Copyright Law. The Copyright Law provides moral and economic rights protection to creators, which includes recognition of the work as well as the exclusive right to obtain economic benefits. Infringement occurs when content is monetised without the consent of the copyright owner. This research analyses the legal protection of copyright on video reaction under the Copyright Law, using a normative approach. The results show that lack of public education and weak law enforcement exacerbate infringement. Solutions include strengthening regulations, strict law enforcement, as well as the active role of digital platforms in providing copyright protection mechanisms. Hopefully, this study contributes to copyright protection in the digital era.